2019
DOI: 10.1002/jrs.5747
|View full text |Cite
|
Sign up to set email alerts
|

Photonic nanojet mediated Raman enhancement: Vertical Raman mapping and simple ray matrix analysis

Abstract: A new method for enhancing the Raman scattering signal has emerged recently, based on dielectric enhancement. Especially promising is the dielectric method based on microspheres and photonic nanojet. In this paper, geometrical aspects and the influence of the incident beam parameters on Raman enhancement by silica microspheres were systematically investigated in three steps: by characterizing the incident beam using knife-edge method, performing horizontal and vertical Raman mapping imaging, and analyzing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…We also demonstrated that the contact mode (i.e., Δ d = 0) achieves the best Raman signal enhancement (Figure S7, Supporting Information). These results are in accordance with previous calculation results, [ 27 ] suggesting that the dielectric microsphere size, NA of the collection lens, and microsphere‐sample distance are all important parameters for PNJ‐based Raman enhancement.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We also demonstrated that the contact mode (i.e., Δ d = 0) achieves the best Raman signal enhancement (Figure S7, Supporting Information). These results are in accordance with previous calculation results, [ 27 ] suggesting that the dielectric microsphere size, NA of the collection lens, and microsphere‐sample distance are all important parameters for PNJ‐based Raman enhancement.…”
Section: Resultssupporting
confidence: 93%
“…An innovative method that enables imaging of specific regions of the sample surface is to trap polystyrene microspheres in water and achieve high-resolution Raman imaging through the optical tweezers mechanism. [24] In atmospheric environments, examples have also been demonstrated to attach dielectric microspheres as a scanning probe to specific locations and scan the sample surface, [25][26][27][28][29][30] among which an atomic force microscope (AFM) cantilever was introduced as one of the elegant mechanical holders for a microsphere. [28] However, the majority of these works applied the scanning microsphere to conventional optical microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the authors [74] for the first time achieved the enhancement of Raman scattering from a silicon wafer using close-packed micron and submicron spherical silica particles. So a new method, microsphere-enhanced Raman spectroscopy (MERS), appeared [75,76].…”
Section: Microlenses In Different Types Of Optical Microscopy and Spe...mentioning
confidence: 99%
“…However, there are very limited and clearly insufficient investigations of the role of tangential electric field components in the spatial and electromagnetic properties of the PJ. It could be noted that, in recent years, the studies in the field of the PJ effect based on the wavelength-scaled dielectric particles have gained more and more popularity and have found numerous applications, including optical trapping [23], nano-fabrications, and surface nano-patterning [24], quantum dot writing [25], microsphere-assisted microscopy and interferometry [26,27], auxiliary optomechanical manipulation [28], surface-enhanced Raman scattering [29], optical waveguides and switching [30,31], and biosensing [32], to name a few.…”
Section: Introductionmentioning
confidence: 99%